The Effect of Cooperative Learning Models on The Students' Mathematical Critical and Creative Thinking Ability: Meta-Analysis Study - Siagian, Qania Agustika; Darhim, Darhim; Juandi, Dadang (Mathematics Education Study Program, 2023)
This study aims to describe the results of the study and examine the effect of the implementation of the Cooperative learning model on the students' mathematical critical and creative thinking abilities and obtain an effect size when viewed based on educational level, sample size, and research demographics from the primary studies being analyzed. This research is quantitative research with a meta-analysis research design. The research sample that met the inclusion criteria consisted of 34 primary studies of mathematical critical thinking ability (the total effect size of the studies was 39) and 23 primary studies of mathematical creative thinking ability (the total effect size of the studies was 24). Based on the research findings, it was found that the overall effect of the implementation of the cooperative learning model on the students' mathematical critical thinking skills had a significant effect with an effect size of 0.792. Overall, implementing the cooperative learning model on the students' mathematical creative thinking ability had a significant effect with an effect size of 0.696. In addition, there is no difference in mathematical creative and critical thinking abilities between the students who studied in the cooperative class and those who studied other than in the cooperative class in terms of education level and sample size. There is no difference in mathematical critical thinking skills between the students who studied in the cooperative class and those who studied other than in the cooperative class in research demography. However, there are differences in mathematical creative thinking abilities between the students who studied in the cooperative class and the students who studied other than in the cooperative class in terms of research demography.